2016
DOI: 10.1111/pai.12518
|View full text |Cite
|
Sign up to set email alerts
|

Maternal psychologic problems increased the risk of childhood atopic dermatitis

Abstract: Postpartum depression increased the risk of childhood AD even when other maternal mental health index and social demographic factors are considered. Early intervention of PPD might be helpful for AD prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 25 publications
(27 reference statements)
2
42
0
2
Order By: Relevance
“…A trend for an inverse association between postnatal depression and AD was also observed. These findings are compatible with several studies on childhood atopic disease associations with maternal prenatal or postnatal stressors [13, 1618, 59, 103], prenatal anxiety but not depression, as suggested above [88, 104107]. Mutual adjustment for anxiety and depression may have uncovered the negative influence of postnatal depression on the health care utilization for infant care and thus, physician diagnosis of AD [108].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A trend for an inverse association between postnatal depression and AD was also observed. These findings are compatible with several studies on childhood atopic disease associations with maternal prenatal or postnatal stressors [13, 1618, 59, 103], prenatal anxiety but not depression, as suggested above [88, 104107]. Mutual adjustment for anxiety and depression may have uncovered the negative influence of postnatal depression on the health care utilization for infant care and thus, physician diagnosis of AD [108].…”
Section: Discussionsupporting
confidence: 90%
“…Infants whose caregivers are less sensitive have higher levels of cortisol [33, 88] and excess cortisol exposure during early infancy may influence the developing immune response via epigenetics or neuroendocrine dysregulation, potentially leading to AD [87, 89, 90]. It is also possible that more sensitive mothers take greater care of their infants’ skin, by for example, use of moisturizer and regular bathing; however, how this may contribute to the atopic march toward asthma is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some studies have indicated that maternal stress during pregnancy may play a significant role in the development of AD in offspring. It is possible that in cases where pregnant women suffer not only from AD but also from depression or psychosomatic disorders, the offspring have a significantly higher risk of developing AD up to the age of 18–20 years . Possible psycho‐immunological pathways are changes in cytokine levels or oxidative stress transferred by the placenta .…”
Section: Factors That May Explain Change In Atopic Dermatitis Severitmentioning
confidence: 99%
“…It is possible that in cases where pregnant women suffer not only from AD but also from depression or psychosomatic disorders, the offspring have a significantly higher risk of developing AD up to the age of 18-20 years. [27][28][29][30][31][32][33][34] Possible psycho-immunological pathways are changes in cytokine levels 21 or oxidative stress transferred by the placenta. 35 Psychosocial job strain in general and alcohol intake during pregnancy in particular 36,37 are significant risk factors for AD development in offspring, with alcohol intake being the most prominent risk factor.…”
Section: Factors That May Explain Change In Atopic Dermatitis Severitmentioning
confidence: 99%